1988
DOI: 10.1002/hlca.19880710508
|View full text |Cite
|
Sign up to set email alerts
|

A Vibrational Study of Some 1,2,4‐Trioxanes

Abstract: The vibrational spectra of some 1,2,4-trioxanes present two characteristic bands at 790 and 880 cm-'. On the basis of "0-isotopic substitution and comparison with analogous compounds, these bands have been assigned to coupled C-0 and 0-0 stretching modes of the C-0-0 element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the earlier experimental studies [36,37], the O p -O p vibrations were assigned to the bands observed at 722, 831, and 881 cm À1 , the lower frequency band being attributed to the O p -O p stretch. Later, on the basis of the vibrational spectra of some 1,2,4-trioxanes, both cis-and trans-fused, 18 O-isotopically and methyl substituted, Jefford et al [39] recognized the two bands at 780 ± 20 and 880 ± 10 cm À1 -arising from a combination of C-O p and O p -O p stretching vibrations of the O-O-C entity -as the fingerprint of 1,2,4-trioxanes. Thus, the bands at 789 and 876 cm À1 were classified as 'characteristic' bands of 1 [39].…”
Section: Vibrational Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the earlier experimental studies [36,37], the O p -O p vibrations were assigned to the bands observed at 722, 831, and 881 cm À1 , the lower frequency band being attributed to the O p -O p stretch. Later, on the basis of the vibrational spectra of some 1,2,4-trioxanes, both cis-and trans-fused, 18 O-isotopically and methyl substituted, Jefford et al [39] recognized the two bands at 780 ± 20 and 880 ± 10 cm À1 -arising from a combination of C-O p and O p -O p stretching vibrations of the O-O-C entity -as the fingerprint of 1,2,4-trioxanes. Thus, the bands at 789 and 876 cm À1 were classified as 'characteristic' bands of 1 [39].…”
Section: Vibrational Modesmentioning
confidence: 99%
“…The IR and Raman techniques have been applied to probe the vibrational modes in the 1,2,4-trioxane ring (C) of 1, especially of the endoperoxide moiety [36][37][38][39]. In the earlier experimental studies [36,37], the O p -O p vibrations were assigned to the bands observed at 722, 831, and 881 cm À1 , the lower frequency band being attributed to the O p -O p stretch.…”
Section: Vibrational Modesmentioning
confidence: 99%
“…11 The FTIR modes in the 700-1200 cm - Computational studies on the radical intermediates will enable us to reveal the details of their structures, stability, and reactions. Such information on the radical transfer-ring process will be helpful in understanding the bio-action phenomena of compounds 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Going to 1,2,4-trioxane, the rigid cyclic structure of the twist boat conformation is reminiscent of that enclosed in artemisinin. 24 The O-O stretching mode is predicted with the strongest Raman intensity at 842 cm 1 . Other three Raman active modes are calculated at 565, 866 and 898 cm 1 .…”
Section: Vibrational Calculationsmentioning
confidence: 99%
“…22,23 Vibrational results on cis-fused derivatives of trioxane O 1 -O 2 Ð Ð ÐO 13 Ð Ð ÐC 12a have provided additional information in a similar peroxide structure. 24 Also, the Fourier transform (FT)-Raman spectrum of (1) has been reported, though not discussed in much detail. 25 The question is open as to how a vibrational assignment as complete as possible might be reached, due to the structural complexity of (1).…”
Section: Introductionmentioning
confidence: 99%